Analisis Tantangan dan Peluang Pengembangan Akuntansi Syariah Untuk Meningkatkan Kinerja UMKM di Indonesia - Rais Abrar Syam; Nur Afinah Syakilah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the challenges and opportunities of developing Islamic accounting in improving the performance of MSMEs in Indonesia, given the strategic role of MSMEs as the backbone of the national economy and the urgent need for a financial management system that is transparent, accurate, and in accordance with Islamic principles. The research uses a descriptive qualitative approach with a literature review method to collect and analyze literature related to the application of Islamic accounting, implementation constraints, and relevant development strategies for MSMEs. The results of the study show that although MSMEs have begun to adapt to digitalization, the majority still use manual recording and face obstacles in literacy, costs, infrastructure, and understanding of sharia principles, while implementation opportunities arise from MSME interest, support from sharia financial institutions, access to halal markets, digitalization, and support networks. In conclusion, the development of Islamic accounting integrated with literacy, technology, and institutional collaboration strategies can improve the professionalism, transparency, and financial performance of MSMEs in a sustainable manner, while strengthening the legitimacy of businesses in modern and halal markets.